Deconvolution analysis improves real-time OSL of BeO ceramic. (December 2021) - Madden, Levi; Lukas, Erin; Santos, Alexandre; Ganija, Miftar; Veitch, Peter; Rosenfeld, Anatoly; Li, Enbang
Abstract: A novel method is presented to correct the non-linearity of real-time optically stimulated luminescence (rtOSL), investigated for a fibre-coupled BeO dosimetry system. The presented method applies novel kinetic modelling techniques to model the time-resolved optically stimulated luminescence, and least squares deconvolution to transform the measured rtOSL into the absorbed dose in BeO. This correction, termed the deconvolution correction, is compared against the Δ rtOSL and exponential correction methods. These rtOSL correction methods multiply the measured rtOSL by a correction function. In the Δ rtOSL correction, this correction function is theoretically derived, whereas the exponential correction approximates the correction function as an exponential growth with respect to time. The deconvolution correction method had a mean dose difference of 1.5%, improving upon the 4.4% and 4.1% achieved by the Δ rtOSL and exponential correction methods, respectively. These prior methods correct the measured rtOSL through multiplication with a sensitivity correction function. The deconvolution corrected responses were characterised by a 1.9% standard deviation with the expected doses, and an average root mean squared error (RMSE) of 2.0% between the corrected rtOSL signal and the modelled time-dependent accumulated dose. In comparison, the Δ rtOSL had a standard deviation of 6.4% and an average RMSE of 7.3% between the corrected rtOSL signal and the modelled time-dependent accumulated dose, while the exponential correction had a standard deviation of 5.4% and a 4.6% average RMSE between the corrected rtOSL and the time-dependent accumulated dose. To determine whether the deconvolution was feasible for real-time correction of measured rtOSL, a computational simulation of the real-time measurement and correction was performed. The maximum computation time for the deconvolution correction was 18 ms, demonstrating that the deconvolution correction is feasible for real-time correction of the rtOSL. Highlights: A real-time optically stimulated fibre-coupled BeO dosimeter was developed. Novel theory of a generalised model for time-resolved luminescence was presented. A novel rtOSL correction was investigated, compared with other correction methods. Deconvolution analysis outperformed the other rtOSL correction methods. rtOSL was shown to be stem free.